Translating “Muhammad Al-Fatih: Perang Varna” Into English - Zakiah Mahmudah; Hasbi Hasbi; Difiani Apriyanti (Politeknik Negeri Padang, 2017)
This final report explains about the process of comic book translation that the title of comic book is “Muhammad al-Fatih: Perang Varna” which was created by Handri Satria an illustrator from Indonesia. This final project is entitled Translating “Muhammad Al-Fatih: Perang Varna” Comic by Handri Satria from Bahasa Indonesia into English which this final project is one of the requirements for the students of English Department in State Polytechnic of Padang in order to finish their study. This final project is aimed to add the reference of translating a comic. This final report gave the discussion of processes or steps that have to be passed so that the result of translation can be understood easily by the readers. By making this final project, it is quite helpful in applying and comprehending the theories of translation that had been learned. After finishing this final project, it can be concluded that to translate texts the translator must have the adequate vocabularies and wide insight either in specific knowledge or in general knowledge, because the translator’s role is to make people understand the ideas and the meaning of text.